Pengendalian Persediaan Bahan Baku Berdasarkan Klasifikasi ABC dan Model Q - Luqi Aditya; Jauhari Arifin (Universitas Indraprasta PGRI Jakarta, 2023)
PT. KWP is a manufacturing company that produces rotating equipment and manufacture tool components. When producing the products, the company needs at least 30 kinds of raw materials. The company, in the process of procuring raw materials, has not so far carried out a critical item analysis of this type of raw material inventory. This can cause problems when there is an urgent request in determining the type of raw material prioritized to be procured first. The company also often overstocks some of the raw materials they use. The purpose of this study is to provide a solution regarding raw material inventory management in the form of using ABC analysis in classifying raw materials and comparing the total inventory cost of existing conditions and the Q back order model. Based on the results of a study show that from the ABC analysis, there are 6 raw materials for A category, 6 raw materials for B category, and 18 raw materials for C category at PT. KWP. Raw materials with category A are those that need to be prioritized first.Then, the use of Q back order model shows the total inventory cost is lower compared to the company's existing conditions, with raw materials in category A totally providing 12% cost savings of Rp.59,152,456.